A novel PI3K inhibitor PIK-C98 displays potent preclinical activity against multiple myeloma - Zhu, Jingyu (Impact Journals LLC, 2014)
Recent clinical trials have demonstrated targeting PI3K pathway is a promising strategy for the treatment of blood cancers. To identify novel PI3K inhibitors, we performed a high throughput virtual screen and identified several novel small molecule compounds, including PIK-C98 (C98). The cell-free enzymatic studies showed that C98 inhibited all class I PI3Ks at nano- or low micromolar concentrations but had no effects on AKT or mTOR activity. Molecular docking analysis revealed that C98 interfered with the ATP-binding pockets of PI3Ks by forming H-bonds and arene-H interactions with specific amino acid residues. The cellular assays demonstrated that C98 specifically inhibited PI3K/AKT/mTOR signaling pathway, but had no effects on other kinases and proteins including IGF-1R, ERK, p38, c-Src, PTEN, and STAT3. Inhibition of PI3K by C98 led to myeloma cell apoptosis. Furthermore, oral administration of C98 delayed tumor growth in two independent human myeloma xenograft models in nude mice but did not show overt toxicity. Pharmacokinetic analyses showed that C98 was well penetrated into myeloma tumors. Therefore, through a high throughput virtual screen we identified a novel PI3K inhibitor that is orally active against multiple myeloma with great potential for further development.